An Analysis of the Carbon Footprint of On-Campus Activities at President University (Main Campus) - Kurniawan, Aprilian (Jurnal Serambi Engineering, 2025)
Climate change has become a crucial environmental issue in various sectors, including educational institutions. This study aims to analyze total carbon emissions from campus activities based on Scope 1 data, which includes generator set data and campus bus operations (2023). Scope 2 consists of electricity bill data (January-December 2023) obtained from the institution. The study uses a quantitative approach with emission calculations based on secondary energy consumption data and transportation activities, as well as carbon absorption estimates based on vegetation tree species and age identification. The results show that the total carbon emissions from campus activities in 2023 can reach 969,217.03 KgCO₂/year. Meanwhile, the emission absorption capacity of existing vegetation only reaches 774,546.11 KgCO₂ per year. Thus, there are residual emissions of 194,670.92 KgCO₂ per year that are not absorbed. The carbon tax calculation of IDR 30.00 per kg of CO₂, according to the prevailing regulations in Indonesia, provides an economic picture of IDR 5,840,127.6 per year for campuses. This finding indicates that campus vegetation has not fully offset the resulting carbon footprint and serves as an important basis for developing emission mitigation strategies towards a more sustainable campus.